Pengaruh Financial Literacy, Financial Self-Efficacy dan Social Economy Status terhadap Perilaku Manajemen Keuangan pada Prajurit Yonarmed 2/Ks Medan - Atletica, Sellyanna Putri; Sembiring , Ferikawita M. (Syntax Corporation, 2025)
This study aims to analyze the influence of financial literacy, financial self-efficacy, and social economy status on financial management behavior among soldiers of Battalion Armed 2/Kilap Sumagan. A quantitative approach was used with multiple linear regression methods to examine the relationships between these variables. The findings indicate that financial literacy, financial self-efficacy, and social economy status have a positive and significant impact on financial management behavior both individually and simultaneously. These results highlight the importance of financial knowledge, confidence in financial decision-making, and socio-economic conditions in shaping better financial management habits. The implications of this research can serve as a basis for policies aimed at enhancing financial literacy and effective financial management among soldiers.